Leveraging chatbot applications to enhance English language learning in Nigerian secondary schools - Jegede, Olusegun Oladele (English Learning Innovation, 2024)
This study explores the potential of chatbot applications to enhance English language learning in Nigerian secondary schools, motivated by the ongoing challenges in achieving high English proficiency using traditional methods. The purpose of the study was to assess the current level of English proficiency among students, evaluate the effectiveness of chatbot applications, understand user perceptions, and identify implementation challenges. A quantitative research design was employed, involving 150 students from three international schools, selected through stratified random sampling. Data were collected using a structured questionnaire and analyzed using descriptive and inferential statistics, along with thematic analysis for qualitative insights. The study revealed varied levels of English proficiency among students’ general positive perceptions of chatbot applications as effective tools for learning English; significant technical and accessibility challenges, such as poor internet connectivity and limited device availability; and the necessity of comprehensive training for both students and teachers to maximize the benefits of chatbot applications. The study concludes that while chatbot applications have considerable potential to improve English language skills, addressing the identified challenges is crucial. Recommendations included enhancing infrastructure, providing comprehensive training, and improving the software and user interface of chatbot applications to maximize their educational benefits. These insights aim to inform educators, policymakers, and technology developers on optimizing the use of chatbot applications in language education.